2015
DOI: 10.5194/bg-12-1431-2015
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal survey of the composition and degradation state of particulate organic matter in the Rhône River using lipid tracers

Abstract: Abstract. Lipid tracers including fatty acids, hydroxyacids, n-alkanols, sterols and triterpenoids were used to determine the origin and fate of suspended particulate organic matter (POM) collected in the Rhône River (France). This seasonal survey (April 2011 to May 2013) revealed a yearround strong terrestrial higher-plant contribution to the particulate organic matter (POM), with significant algal inputs observed in March and attributed to phytoplanktonic blooms likely dominated by diatoms. Major terrigenous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 74 publications
(92 reference statements)
1
19
0
1
Order By: Relevance
“…Previous results obtained in the Rhône [5] and Mackenzie [6] Rivers clearly showed that the SPM of terrestrial origin found in major coastal rivers has been intensely autoxidized even before reaching the ocean, but the results obtained in this study confirm that metal ions present in the water have favored this autoxidation, and will favor it in seawater. In coastal environments, it is possible that the metal ions necessary to induce this autoxidation could be desorbed from SPM upon its arrival at sea [15,16].…”
Section: Rhone River Spm Incubationssupporting
confidence: 52%
See 4 more Smart Citations
“…Previous results obtained in the Rhône [5] and Mackenzie [6] Rivers clearly showed that the SPM of terrestrial origin found in major coastal rivers has been intensely autoxidized even before reaching the ocean, but the results obtained in this study confirm that metal ions present in the water have favored this autoxidation, and will favor it in seawater. In coastal environments, it is possible that the metal ions necessary to induce this autoxidation could be desorbed from SPM upon its arrival at sea [15,16].…”
Section: Rhone River Spm Incubationssupporting
confidence: 52%
“…Because sitosterol alone cannot be unambiguously attributed to organic matter of terrestrial origin (possible production by freshwater plankton [5]), we have compared its autoxidation rates to those of other compounds of a more clearly terrestrial origin. In all incubations, we determined autoxidative degradation rates for three families of lipid tracers: sitosterol, α-/β-amyrins, and betulin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations